Mechanisms of asphalt mixture rutting in the dry Hamburg Wheel Tracking test and the potential to be alternative test in measuring rutting resistance - Chaturabong, Preeda; Bahia, Hussain U. (Construction & building materials, 2017)
•The dry Hamburg Wheel Tracking (HWT) test is proposed in measuring the rutting resistance of asphalt mixtures.•The dry HWT test can simulate rutting mechanisms including densification and shear failure analyzed by image processing analysis system 2 (IPAS2).•The dry HWT test shows a strong correlation of creep slope and cumulative strain with equivalent cycles observed for FN test. Rutting is one of the most important failures occurring in hot mix asphalt (HMA) especially in the summer season and slow moving traffic areas. Rutting is a pavement surface failure compromising the safety and ride comfort of traveling and thus needs to be accurately evaluated in a laboratory. Although the flow number (FN) test is commonly used for evaluating the rutting resistance of HMA in a laboratory, there are some shortcomings in using FN test such as the costly and complicated equipment. Another potential test that is likely to be more advantageous than the FN test for evaluating the rutting resistance is the Hamburg Wheel Tracking (HWT) test, however, it is typically conducted in wet condition, and inadequate results in dry condition have been reported. The objective in this study is to optimize the HWT test subject to dry condition to be one potential method in measuring rutting resistance in a laboratory. Two rutting mechanisms (densification and shear failure) of HMA samples conducted in the HWT device were determined by Image Processing and Analysis version 2 (IPAS2). Results indicate that HMA samples under the dry HWT test can exhibit both rutting mechanisms in which typically occur in the field. Also, the dry HWT test shows a very good R2 for a relation of creep slope with the confined and unconfined FN test. As a result, the dry HWT can be an effective tool of quantifying rutting potential with better simulating to field behavior, lower cost of equipment, and less complicated geometry that can also accommodate field cores.